GEGURITAN (MANUSCRIPT) OF I GEDE BASUR AND I KETUT BUNGKLING WRITTEN BY KI DALANG TANGSUB: INTERTEXTUAL AND RECEPTIONAL ANALYSIS - Suardiana, I Wayan; Kutha Ratna, Nyoman; Cika, I Wayan; Suastika, I Made (e-Journal of Linguistics; Vol. 3. Juli 2009 No. 2, 2009)
This study employs the texts of I Gede Basur and I Ketut Bungkling contained inthe text of Kidung Prembon (abbreviated into KP) as the data source to explain theintertextual relationship and receptive process of the texts of Geguritan I Gede Basur(abbreviated into GIGP) and Geguritan I Ketut Bungkling (abbreviated into GIKB)written by Ki Dalang Tangsub. The reason is that when this study was conducted theneither the text of GIGB nor GIKB written by the authoritative Ki Dalang Tangsub wasfound. Then the text of KP has multiple functions; on one side, as an existing text, it isassumed to contain the texts of GIGB and GIKB written by the authoritative Ki DalangTangsub, and on the other side, it is a receptive text of the texts of GIGB and GIKBwritten by Ki Dalang Tangsub.The theories of intertexts, reception and discourse were used as the means ofanalysis in this study. The theory of intertexts could reveal the historical process of thetexts of GIGB and GIKB written by Ki Dalang Tangsub and the creation process of thetext of KP. The theory of reception was basically used to explain the process of how thereaders gave responses to the texts of GIGB and GIKP written by Ki Dalang Tangsub.The process of how the readers gave responses was revealed by the text of KP (in clockstories) as well as the other individual texts.Intrinsically, the texts of GIGB and GIKB written by Ki Dalang Tangsub giveparticular colors to the texts of the responses given, as Pupuh/Tembang Ginada (strophe)is entirely adopted in the texts of responses given the readers making the particularcharacteristics of the hypogram texts compared to the following texts clear. Havingmagical and social critical themes, many hyperboles, similes and sarcasms are used in thetexts of GIGB and GIKB written by Ki Dalang Tangsub. The plots of the texts of GIGBand GIKB are made up of 28 big sequences and 29 small sequences with the maincharacters are I Gede Basur and I Ketut Bungkling (Mantri as one of the characters).
Keywords: intertexts, reception, GIGB and GIKB, KP, the dominant concepts (ideology)